Investigation of Chemical Treatments to Enhance the Mechanical Properties of Natural Fiber Composites - Farooq Rauf; Muhammad Umair; Khubab Shaker; Yasir Nawab; Tehseen Ullah; Sheraz Ahmad (International Journal of Polymer Science)
A sustainable approach to composites is leading to the use of natural fibers rather than synthetic materials, like carbon or glass, for reinforcement. However, the higher moisture absorption of natural fibers impairs the composite’s mechanical properties. Therefore, to improve the mechanical properties, some chemical treatments like silane and fluorocarbon can be performed to reduce the moisture absorption of natural fibers. In this study, flax was used as reinforcement, and epoxy was used as a matrix. In the first part of the study, flax reinforcement was treated with different concentrations of silane (20, 40, and 60 g/L) and fluorocarbons (80, 100, and 120 g/L). Moisture regains (MRs), absorbency, and tensile strength were measured at reinforcement levels. According to the results, reinforcements treated with 60 g/L silane (S3) and 120 g/L fluorocarbons (F3) exhibited the lowest MR values of 7.09% and 3.06%, respectively, whereas water absorbency was significantly reduced. The sample treated with 120 g/L fluorocarbons required 300 seconds extra time to absorb the water as compared with the untreated sample, whereas samples S3 and F3 showed an increase in tensile strength by 20.16% and 34.80% when compared with untreated reinforcement flax reinforcement. In the second part of the study, untreated and treated flax reinforcements were combined with an epoxy matrix for composite fabrication. MR and mechanical tests (tensile, flexural, and Charpy impact tests) were performed. Results revealed that treated flax-reinforced composites exhibited lower MR values 0.86% for F3 and 0.42% for S3, respectively. The tensile, flexural, and pendulum impact strengths of silane-treated reinforced composite sample C.S3 were increased by 15.07%, 117%, and 20.01%, respectively, compared with untreated reinforced composite samples. Consequently, both chemical treatments improve composite mechanical performance as well as service life.